La migración y la construcción del Otro como enemigo: Una Reflexión Filosófica - Bertani, Maria Luisa (2026)
Contemporary migratory flows since the 20th century have undergone a radical metamorphosis, revealing unprecedented aspects of migratory phenomena that require complex reflection. Definitions and conceptualizations of the “other”, “foreigner”, “migrant”, are social and institutional constructions of the figure of the migrant. A deep philosophical reflection can lead to a debate on how conceptions of the “migrant” are intertwined with structures of power, domination and processes of inclusion and exclusion. The aim of this research is to critically analyze the construction of the “other” as an enemy in the context of migration, probing the different discursive tactics and mental representations of reality used to legitimize exclusion against migrants. The present research is an interpretation of philosophy developed with an analytical-linguistic and hermeneutic method. In addition, the article proposes a reflection that can foster a concrete philosophy of migration by outlining practical responses to a period of extreme contingency.